2015
DOI: 10.2169/internalmedicine.54.3256
|View full text |Cite
|
Sign up to set email alerts
|

XPD Lys751Gln Polymorphisms and the Risk of Esophageal Cancer: An Updated Meta-Analysis

Abstract: Objective Published data regarding the association between xeroderma pigmentosum group D XPD Lys751 Gln polymorphisms and esophageal cancer (EC) cancer remain controversial. The present meta-analysis aimed to obtain a more precise estimation of the relationship between XPD Lys751Gln polymorphisms and the risk of EC. Methods All eligible case-control studies of Lys751Gln polymorphisms and susceptibility to EC were selected from PubMed, Web of Science and CNKI up to October 2013. The data were extracted, and poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Xue et al (2012) conducted a meta-analysis with 12 case-controls studies and found that the ERCC2 rs13181 polymorphism is correlated with an increased risk of gastric cancer. Guo et al (2015) conducted a meta-analysis with 21 case-control studies and reported that theERCC2 rs13181 polymorphism contributes to susceptibility to esophageal cancer. Li et al (2014) performed a meta-analysis and reported that the ERCC2 rs13181 polymorphism is associated with susceptibility to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xue et al (2012) conducted a meta-analysis with 12 case-controls studies and found that the ERCC2 rs13181 polymorphism is correlated with an increased risk of gastric cancer. Guo et al (2015) conducted a meta-analysis with 21 case-control studies and reported that theERCC2 rs13181 polymorphism contributes to susceptibility to esophageal cancer. Li et al (2014) performed a meta-analysis and reported that the ERCC2 rs13181 polymorphism is associated with susceptibility to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The rs13181 polymorphism of ERCC2 is a T to G substitution at the 751 locus, which may alter the enzymatic activity of the encoded protein. ERCC2 rs13181 is associated with various cancers, such as gastric cancer, esophageal cancer, non-small cell lung cancer, hepatocellular carcinoma, prostate cancer, skin cancer, and bladder cancer (Yin et al, 2013;Zhu et al, 2013;Li et al, 2014;Ramaniuk et al, 2014;Zhu et al, 2014;Yang et al, 2015;Guo et al, 2015). Previous studies have reported the association between the ERCC2 rs13181 polymorphism and glioma development, but the results are inconclusive (Caggana et al, 2001;Wrensch et al, 2005;Yang et al, 2005;Liu et al, 2009;Luo et al, 2013;Rodriguez-Hernandez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To date, molecular epidemiological studies on two GSNPs in this gene, namely, rs369191500 polymorphism (codon 312, Asp to Asn) and rs13181 polymorphism (codon 751, Lys to Gln), have been conducted by diferent laboratories [54]. Genotype-phenotype analyses have shown that these two GSNPs are associated with low DNA repair ability, which might modify DNA-adduct levels, p53 gene mutation, and risk of cancer [55,56]. For genetic polymorphisms among Guangxiese population, a total of four epidemiological studies have been conducted via case-control design ( [58].…”
Section: Xeroderma Pigmentosum D (Xpd) Gsnps and Afb1-hcc Among Guangmentioning
confidence: 99%
“…For 51 SNPs identified by meta‐analysis, 38 SNPs had statistically significant association with EC or ESCC susceptibility . Meta‐analysis results showed that there were 27 SNPs associated with increased EC or ESCC risk, whereas 11 SNPs decreased the risk of EC or ESCC risk.…”
Section: Resultsmentioning
confidence: 94%